Analysis of the implementation of the Kurikulum Merdeka in high school physics learning activities - Badriah, Iklimah; Adimayuda, Rizal (Research in Physics Education, 2024)
The implementation of the Kurikulum Merdeka presents challenges for educational units that adopt it. In physics learning, students often engage in projects that start with problem-solving. Therefore, this study aims to understand the implementation of the Kurikulum Merdeka in high school physics learning activities. This research uses a qualitative descriptive method with a case study approach, utilizing questionnaires and interviews for data collection, and data analysis through questionnaires. Interview data is analyzed using thematic analysis. The sample is selected using purposive sampling with participants spread across 4 schools, 4 physics teachers, and 160 students offline. The results of the questionnaire data show that students agree with the Kurikulum Merdeka from the aspect of using teaching tools, with 92% agreeing and 8% strongly agreeing; however, textbooks and worksheets are rarely used. From the aspect of project strengthening of the Pancasila student profile, 87% agree and 13% strongly agree. Interview results reveal that students do not fully understand the physics concepts within the projects. From the aspect of learning outcomes, 91% agree and 9% strongly agree. In contrast, interview results with teachers indicate that teaching tools are created according to the school’s conditions. Furthermore, the implementation of Pancasila student profile in the context of physics learning is not directly related to the physics subject but is mandatory for educational units. Learning outcomes in physics involve spirituality, independence, teamwork, global diversity, and critical thinking.